Endogenous labor supply and trade - Tadashi Morita; Takanori Ago; Takatoshi Tabuchi; Kazuhiro Yamamoto (European Regional Science Association (ERSA), 2015)
It is assumed in new trade theory and new economic geography that the supply of labor is fixed, which is not true in real labor markets. We develop a model of new trade theory by incorporating an elastic labor supply and analyze the impacts of technological progress on the equilibrium outcomes of working hours and economic welfare. We first show that the labor supply curve is backward bending. We then show that working hours in developed countries are longer in the first stages of development, but shorter in the second stages of development.
Keywords: F10; R10; 330; international trade; variable markup; endogenous labor supply